2019
DOI: 10.1002/cncr.32129
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of hepatocellular carcinoma among older Americans attributable to hepatitis C and hepatitis B: 2001 through 2013

Abstract: Background In the United States, incidence and mortality rates of hepatocellular carcinoma (HCC) are increasing in older individuals. Chronic infection with hepatitis C virus (HCV) and hepatitis B virus (HBV) are important causes of HCC; however, the contribution of viral hepatitis to recent trends in HCC incidence among older Americans is unclear. Methods Data from the Surveillance, Epidemiology, and End Results–Medicare linkage (SEER‐Medicare) for the years 2001 through 2013 were used to identify HCC cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…With the popularization of risk factor screening program and the application of prevention regimens, incidence of HCC has dropped significantly in many regions, such as parts of China and Japan [2]. However, an increasing trend in both incidence and mortality rates of HCC has been observed in many European countries and North America owing to the high prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections [3]. In spite of the considerable number of risk factors identified for HCC, pathogenesis of this disease remains poorly understood [4,5], which is a big challenge in the development of novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…With the popularization of risk factor screening program and the application of prevention regimens, incidence of HCC has dropped significantly in many regions, such as parts of China and Japan [2]. However, an increasing trend in both incidence and mortality rates of HCC has been observed in many European countries and North America owing to the high prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections [3]. In spite of the considerable number of risk factors identified for HCC, pathogenesis of this disease remains poorly understood [4,5], which is a big challenge in the development of novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence trends over the most recent 5-year period (2011-2015) also increased among both males and females for six major racial and ethnic groups in the USA except Hispanic men and API women (both with stable trends) and API men (decreasing trends) (28). Two studies reported increasing HCC incidence across all considered racial/ethnic groups (49,50), and two others found increasing trends for all groups (52,53) except APIs, where trends were either stable (52) or decreasing (53). Age-specific HCC incidence rates also increased from 1992 to 2015 among persons 60 years and older in all racial/ethnic groups except APIs aged 70-79 years, whereas they decreased among ages 40-59 years of all races/ethnicities since the mid-2000s (51).…”
Section: Trends By Race And/or Ethnicity (Usa Only)mentioning
confidence: 92%
“…Patterns for age-specific trends were mixed ( Table 2). There was a suggestion of increasing trends among older adults (≥60 years) in the USA (49)(50)(51)(52)(53), whereas they decreased (53) for persons aged 35-49 years and were stable for younger age groups (53) over at least 10 years from 2000 onwards. One study reported that incidence rates had decreased among both younger (40-49 years) and middle-aged (49-53, 55, 57, 59, 61, 63) adults since around mid-2000s to 2015 (51).…”
Section: Trends By Agementioning
confidence: 99%
See 2 more Smart Citations